Timor Leste and Austrslia Historic Agreement on Maritme Borders in Timor Sea - Putri Citra (Universitas Duta Bangsa Surakarta, 2023)
Maritime borders are an important issue for every country to protect including each territorial waters wealth. The issue of Timor Leste and Australia has become a big issue in the history of the International Court of Justice regarding the agreement of maritime boundaries in the Timor Sea. In this study, the author uses normative juridical research to discuss the Timor Sea agreement as the result between Timor Leste and Australia’s boundary about maritime borders and how Timor Leste gets 90% and Australia gets 10% of the total exploitation of oil and gas. This study also uses library research to complete the data. Both countries Timor Leste and Australia areas are beyond the authority of the authors. This analysis from the authors provides qualitative for future analysis or research.